STRATEGI PERMINTAAN DALAM BAHASA MINANGKABAU: TINJAUAN DARI PERSPEKTIF JENDER - Melly Siska Suryani (BASIS (Bahasa dan Sastra Inggris), 2016)
This study aims at describing request strategies based on gender perspective. The study was conducted by collecting data, analyzing data dan presenting the result of analysis. The data were obtained by using observation, recording and note taking technique. They were 40 informants involved, 20 male and 20 female. Having collected the data, they were analyzed by using referential method, translational and pragmatic identity method. Futhermore, the result of analysis was presented in formal and informal method. The analysis indicated that there were eight forms used : direct utterance, indirect utterance, literal utterance, non literal utterance, direct literal utterance, indirect literal utterance, direct non literal utterance, and indirect non literal utterance